Reinventing Corrective Feedback Strategies In A Higher Education Academic Writing Synchronous Course - Dwi Rahayu; Eka Margianti Sagimin (Universitas Cokroaminoto Palopo, 2024)
Corrective feedback (CF) for academic writing is essential to improve writing skills. This study discovers how CF strategies are reinvented in an academic writing synchronous course. Therefore, within the framework of sociocultural and humanistic approaches in education, 71 students from two non-quasi classes in a university contributed by sharing their points of view for the CF they received. Class observations and surveys were conducted to gather data on how the CF was given and how the students perceived it. The main findings indicate that the CF was choral to the class, explicit, unfocused, and mixed of oral and written. Furthermore, peer reviews were conducted as the follow-up activity. Through these CF strategies, most participants have positive acceptance and comprehension. They also approve that their academic writing skills improved after the course ended. Despite a small number of students who preferred a direct one-on-one basis, this research shows pedagogical CF strategies and efficacies towards independent learning that are prevalent and feasible to the continuous online or hybrid learning systems nowadays.